Printability and heat induction via magnetism of 4D printed iron oxide shape memory polymer composite - Chiew, Guang Hui (Nanyang Technological University, 2022)
The aim of this Final Year Project (FYP) is to evaluate the feasibility of printing Iron (II, III) Oxide (Fe3O4)-filler Shape Memory Polymer (SMP) using a 3D printing technology called Digital Light Processing (DLP) that utilizes a Vat Polymerization process. Furthermore, the effects of increasing Fe3O4 particle loading on the material properties and the viability of heat generation of Fe3O4-filler SMP will be examined in this project.